Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.